Technical Assessment of the Condition of Paved Cantonal Road Networks - López, Sharline (2025)
A five year plan is an important instrument for road management. It can provide a schedule for the maintenance and rehabilitation activities; also this provides a guide to calculate the budget necessary for the annual projects. You need to know the network and its condition to determinate the appropriate intervention and control the progress every year.Evaluation within urban municipalities has been on a priority basis in the main routes of the region, which placed vehicle counters, with which it was possible to determine the amount and kind of vehicles circulating. Made a surface condition evaluation was performed (VIZIR), as well as a structural evaluation (FWD) and functional (IRI) assessment of different routes, this evaluation evidence their bad condition. In addition some test pits were performed at strategic sites which made it possible to characterize the structure that comprises the pavement and identify the types of soil that predominate in the structures of the municipal roads.A Georeferenced database is one of the main products generated from the evaluation of the network, since it allows to evaluate the condition at the macro level, not just level network project, facilitating the process of prioritization of road maintenance for the network.A key element for defining and implementing a pavement management system is the staff which is in charge of this, specifically, the technical unit of municipal road management. Members of this unit must be properly trained and dedicate full time to road work and planning.